Implementation of Regression Analysis to Test the Effect of Social Media, Work Motivation, Work Discipline on Increasing the Performance of Sipare-Pare Tengah Village Office Employees, Marbau District, North Labuhanbatu Regency - Sanjaya, Mahmud Azi; Prayoga, Yudi; Halim, Abd. (JINAV: Journal of Information and Visualization, 2023)
The purpose of this study was to determine and analyze the influence of social media, work motivation, work discipline on improving employee performance at the Sipare-Pare Tengah Village Office. The research method used in this study is a quantitative research method. This research also includes quantitative research that is correlational. The population in this study were all employees at the Sipare-Pare Tengah Village Office with a total of 44 people. The number of samples used in this study amounted to 44 people. Where the entire population is used as a research sample using the saturated sample method. The data used in this study is primary data, namely data obtained directly by researchers from measuring the length of the short intervals in the measuring instrument is the Likert scale. The data analysis technique used in this study is a quantitative data analysis technique using statistical methods. This study uses the calculation results of the IBM Statistical Package For The Social Science (SPSS) version 26 which aims to determine the significant level and relationship between the independent variables and the dependent variable. Partially, the social media variable (X1) has a positive and significant effect on the performance improvement variable by tcount value 2,636 > ftable 1,684 with a significant value of 0.215 > 0.05. Partially, the work motivation variable (X2) has a positive and significant effect on performance improvement variables with a tcount of 2,089 > ftable of 1,684 with a significant value of 0.000 <0.